2016
DOI: 10.1186/s12872-016-0361-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy, safety and tolerability of Ambrisentan in Chinese adults with pulmonary arterial hypertension: a prospective open label cohort study

Abstract: BackgroundAlthough several new drugs have been approved in recent years, pulmonary arterial hypertension (PAH) remains a rapidly progressive disease with a poor prognosis. Ambrisentan, a selective endothelin type A antagonist, has been approved for treatment of PAH. This open label study assessed the efficacy and safety of ambrisentan in Chinese subjects with PAH.MethodsEligible patients with PAH (World Health Organisation [WHO] functional class [FC] II orIII) were enrolled and received Ambrisentan (5 mg) once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 15 publications
3
18
1
Order By: Relevance
“…An open-label, phase IIIb, single-arm study was conducted in China in patients with PAH between 21 December 2012 and 15 August 2014 (NCT01808313). The detailed study design and results of the study have been reported elsewhere [17]. This post-hoc analysis was conducted using a subgroup of patients with CTD-PAH and IPAH/HPAH.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…An open-label, phase IIIb, single-arm study was conducted in China in patients with PAH between 21 December 2012 and 15 August 2014 (NCT01808313). The detailed study design and results of the study have been reported elsewhere [17]. This post-hoc analysis was conducted using a subgroup of patients with CTD-PAH and IPAH/HPAH.…”
Section: Methodsmentioning
confidence: 99%
“…This post-hoc analysis was conducted using a subgroup of patients with CTD-PAH and IPAH/HPAH. Briefly, eligible patients received oral 5 mg ambrisentan once daily for 12 weeks in the primary evaluation period, followed by a 12-week dose adjustment period, during which the dose of ambrisentan was titrated to 10 mg depending on patients' dose tolerance [17].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations